Bcmimp1, a Botrytis cinerea Gene Transiently Expressed in planta, Encodes a Mitochondrial Protein - Benito-Pescador, David; Santander, Daniela; Arranz, M.; Díaz-Mínguez, José M.; Eslava, Arturo P.; van Kan, Jan A. L.; Benito, Ernesto P. (Frontiers in Microbiology, 2016)
Botrytis cinerea is a widespread necrotrophic fungus which infects more than 200 plant species. In an attempt to characterize the physiological status of the fungus in planta and to identify genetic factors contributing to its ability to infect the host cells, a differential gene expression analysis during the interaction B. cinerea-tomato was carried out. Gene Bcmimp1 codes for a mRNA detected by differential display in the course of this analysis. During the interaction with the host, it shows a transient expression pattern with maximal expression levels during the colonization and maceration of the infected tissues. Bioinformatic analysis suggested that BCMIMP1 is an integral membrane protein located in the mitochondrial inner membrane. Co-localization experiments with a BCMIMP1-GFP fusion protein confirmed that the protein is targeted to the mitochondria. ΔBcmimp1 mutants do not show obvious phenotypic differences during saprophytic growth and their infection ability was unaltered as compared to the wild-type. Interestingly, the mutants produced increased levels of ROS, likely as a consequence of disturbed mitochondrial function. Although Bcmimp1 expression is enhanced in planta it cannot be considered a pathogenicity factor.